ERRORS ON COHESIVE DEVICES MADE BY SENIOR HIGH SCHOOL IN WRITING NARRATIVE TEX - Lila Aprillia Sugiarto; Adi Yusuf (Journal of Research in Foreign Language Teaching (JRFLT), 2021)
One of important aspects that needs to be considered to make good writing is ‘cohesive device’. It is used to connect the parts of a text. This study is focused on analyzing errors on cohesive devices that are made by senior high school students in writing narrative text. The design of this study was qualitative. It was found that the students made 3 types of errors in using cohesive devices: transitions, pronoun references, and repetition of key nouns consisting of 8 errors of transitions, 4 errors of pronoun, and 6 errors of repetition. Considering the findings, it is expected that teachers formulate a new strategy or ways of corrective feedback to improve students’ writing.